A systematic review of school meal nudge interventions to improve youth food behaviors - Jessica Jarick Metcalfe; Brenna Ellison; Nader Hamdi; Rachel Richardson; Melissa Pflugh Prescott (BMC, 2020)
Abstract Background School meal programs have a large reach and thus are ideal environments in which to implement interventions targeting improved youth eating behaviors and reduced food waste. This systematic review summarizes the evidence on the effectiveness of school meal nudge interventions on influencing children's eating and waste behaviors. Methods Inclusion criteria required studies have participants in primary or secondary school (grades K-12) with interventions that occurred during school lunch or breakfast in the cafeteria and included at least one of the following outcomes: selection, consumption, waste, or school meal participation. Analyses of intervention outcomes were restricted to studies of strong and moderate quality. Results Twenty-nine studies were included in the quality assessment. Included interventions fell into three categories: 1) placement/convenience, 2) marketing/promotion, or 3) variety/portions. The 20 strong and moderate quality studies included in outcome analyses generally used strong data collection methods and study designs, but were limited by an overall lack of intervention fidelity checks. Multi-component interventions often did not use methods that allowed for separate analyses of outcomes for different intervention components. Conclusions School meal nudge interventions were positively associated with food selection, and had an inconsistent relationship with food consumption. There were few studies evaluating the impact of nudge interventions on meal participation or food waste. The limited evidence available links nudges to improved meal participation, as well as undesirable increases in food waste. Future research in this area should use methods that incorporate implementation metrics, attend to systems factors, and allow the outcomes of individual intervention components to be isolated.